MXene/carbonized bagasse fiber aerogel thermal insulation material - Zhu, MengQi; Lin, HaiTao; Shan, Xiaoxiao; Jiang, Yong (AIP advances, 2024)
Since the existence of high-density gas voids, Ti3C2Tx (MXene), especially aerogels, whose diverse surface chemistry and porous hollow structure break the continuity of the heat transmission path and effectively reduce its thermal conductivity, has broad prospects in the field of new thermal insulation materials. Herein, MXene and carbonized bagasse fiber (CBF) are compounded into a special aerogel through hydroxyethyl cellulose, which not only reduces its cost but also improves its thermal insulation and mechanical properties. MXene/CBF aerogels have low thermal conductivity (69 mW·m−1·K−1) and excellent compressive stress (1.04 MPa), which make them to be used in the field of environmental protection and heat insulation materials.